Relationship between hematocrit values in tuberculosis (TB) sufferers who received anti-tuberculosis drug treatment at the Pematangsiantar Raya Community Health Center - Herawati, Noni (Science Midwifery, 2024)
Tuberculosisis a direct infectious disease caused by germs Microbacterium Tuberculosis. Transmission occurs when TB patients cough or sneeze, germs are spread in the air in the form of droplet nuclei. The use of OAT in TB sufferers based on the duration of OAT consumption can cause a decrease in hematocrit values ​​due to side effects of the drug, namely anemia and thrombocytopenia. The method used in this research is descriptive. This study aims to determine the description of hematocrit values ​​in TB sufferers who received OAT treatment at the Pematangsiantar Raya Community Health Center. The sample for this research was 30 people taken randomlypurposive sampling. The results of the study showed that the results of the examination that received OAT treatment at the end of the second month were 24 people (80%), of which the results of the examination showed that the hematocrit value was low as many as 15 people (62.5%), and normal as many as 9 people (37.5%) shows a low hematocrit value. In the examination of patients who received treatment at the end of the sixth month, 6 people (20%) showed examination results with low hematocrit values, 6 people (100%). The low hematocrit value found in TB sufferers at the end of the second and sixth months of treatment is due to the side effects of the OAT consumed, age, gender and the body's immunity in fighting bacteria that attack blood cells, resulting in a decrease in the hematocrit value. It can be concluded that of the 30 TB sufferers who received OAT treatment at the end of the second and sixth months, the number of sufferers with low hematocrit values ​​was greater than those with normal hematocrit values.